The potential of spiced tea for health - Wenny Bekti Sunarharum; Dego Yusa Ali; Tanalyna Hasna; Azzahramidha Pradichaputri; Adnel Nathaniela Sabatudung; Nadyah Eka Nurizza; Muhamad Ibnu Shidqi Farras; Annisa Aurora Kartika (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Tea (Camellia sinensis) is one of the most important commodities in the world, including in Indonesia. Tea products contain polyphenols, an antioxidant beneficial for health. Nowadays, tea product diversification has gain market and increased consumer acceptance due to its functional benefits besides flavour. The use of spices in tea is widely applied not only to add flavour, but also to increase its functional value. Various bioactive components contained in spices can be used as fragrances, flavour enhancers, preservatives, and natural colouring. This review explores the potential benefit of adding spices into tea (Camellia sinensis) to enrich previous studies on tea and to support development of Camellia sinensis-based tea in Indonesia.